2005
DOI: 10.1136/bjo.2004.048314
|View full text |Cite
|
Sign up to set email alerts
|

Iodide iontophoresis as a treatment for dry eye syndrome

Abstract: Background/aims: Among the causes related to the development or perpetuation and aggravation of dry eye disease, oxidative reactions may have a role in the pathogenesis of this disorder. Antioxidants, such as iodide, have shown a strong effect in preventing the oxidative damage to constituents of the anterior part of the eye. In this clinical trial the effectiveness of iodide iontophoresis and iodide application without current in moderate to severe dry eye patients was compared. Methods: 16 patients were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
1
22
0
1
Order By: Relevance
“…Ocuphor (Iomed Inc., USA) and Visulex (Aciont Inc., USA) are the other ocular iontophoresis systems under investigation for trans-scleral iontophoresis. Harwath-Winter et al demonstrated the superiority of ocular iontophoresis for the delivery of sodium iodide in treating dry eye syndrome in 28 patients [99]. The investigators observed no corneal edema or epithelial damage in this study.…”
Section: Key Approaches To Overcome Permeability Barrierssupporting
confidence: 53%
“…Ocuphor (Iomed Inc., USA) and Visulex (Aciont Inc., USA) are the other ocular iontophoresis systems under investigation for trans-scleral iontophoresis. Harwath-Winter et al demonstrated the superiority of ocular iontophoresis for the delivery of sodium iodide in treating dry eye syndrome in 28 patients [99]. The investigators observed no corneal edema or epithelial damage in this study.…”
Section: Key Approaches To Overcome Permeability Barrierssupporting
confidence: 53%
“…Also an improvement in tearfilm break-up time and fluorescein and rose bengal staining of the ocular surface was observed in dry-eye patients after iodide iontophoresis [5] The amount of iodide in the tissues of the ocular surface and a possible depot effect may explain the sustained improvement of dry eye complaints of the patients seen for a longer period of up to 6 months or longer [54]. It was reported that iodide binds to some of the connective tissue components such as collagen [55].…”
Section: Discussionmentioning
confidence: 90%
“…The significant improvement of the antioxidative protective capacity of the tear fluid by iodide iontophoresis in Bad Hall/ Austria is certainly an essential expansion of the treatment of dry eye syndrome, especially in cases with oxidative stress to the ocular surface [5,9,21,31,32,54,57,61,64] Further investigations are needed to elucidate iodine effects on other factors of dry eye disorders, for instance inflammation, which is another important finding in dry eye syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabei wurde mit einem lontophorese-System Iodid in das Auge gebracht and mit einer Kontrollgruppe verglichen, der Iodid ohne Stromanwendung appliziert wurde [104]. In dieser Studie warden 56 Augen von 28 konsekutiven Patienten mit moderatem bis schwerem trockenen Auge, mit oder ohne Sjogren-Sydrom, vor and nach Iodid-Elektrophorese, in einer dreimonatigen Follow-up-Periode untersucht.…”
Section: Klinische Studienunclassified